2009
DOI: 10.1037/a0015578
|View full text |Cite
|
Sign up to set email alerts
|

Assessing traumatic event exposure: Comparing the Traumatic Life Events Questionnaire to the Structured Clinical Interview for DSM-IV.

Abstract: Posttraumatic stress disorder (PTSD) diagnosis requires first identifying a traumatic event, but very few studies have evaluated methods of potential traumatic event assessment and their impact on PTSD diagnosis. We compared a behaviorally-specific comprehensive multiple-item traumatic event measure to a single-item measure to determine their impact on traumatic event identification and subsequent PTSD diagnosis. In a within-subject, counterbalanced design, the Traumatic Life Events Questionnaire (TLEQ; Kubany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 34 publications
4
70
0
1
Order By: Relevance
“…Because these interviews rely on one or very few questions (probes) to screen out cases considered unlikely to have the diagnosis, some sensitivity may be sacrificed. For example, Pierce et al (Peirce, Burke, Stoller, Neufeld, & Brooner, 2009) found that the Structured Clinical Interview for DSM-IV, which utilizes a clinical interviewer but has a single probe for criterion A, identifies fewer traumatic events than the more detailed Traumatic Life Events Questionnaire. Thus, if any bias exists with the CIDI, it would appear to be in the direction of underestimating PTSD.…”
Section: Checklist Vs Structured Interview Assessment Of Ptsdmentioning
confidence: 98%
“…Because these interviews rely on one or very few questions (probes) to screen out cases considered unlikely to have the diagnosis, some sensitivity may be sacrificed. For example, Pierce et al (Peirce, Burke, Stoller, Neufeld, & Brooner, 2009) found that the Structured Clinical Interview for DSM-IV, which utilizes a clinical interviewer but has a single probe for criterion A, identifies fewer traumatic events than the more detailed Traumatic Life Events Questionnaire. Thus, if any bias exists with the CIDI, it would appear to be in the direction of underestimating PTSD.…”
Section: Checklist Vs Structured Interview Assessment Of Ptsdmentioning
confidence: 98%
“…The well-validated TLEQ is considered the "gold standard" of traumatic event assessments, 23,24 and appears preferable to other measures of traumatic events in drug user populations. 1 It contains a comprehensive list of 22 behaviorally descriptive potential traumatic events (and a 23rd category of "other events" with examples) to assess the DSM-IV criterion A(1) for PTSD. 21 The following question for adult physical assault is an example of the type of questions on the assessment: "Have you been robbed or been present during a robbery where the robber(s) used or displayed a weapon?"…”
Section: Assessmentsmentioning
confidence: 99%
“…Indeed, drug users have one of the highest rates of PTSD among any clinical population, with most prevalence estimates ranging over 25%. 1,2 PTSD and other psychiatric disorders precipitated by traumatic events convey considerable disease burden to drug users, through the direct effects of psychiatric symptoms and the indirect effects of these symptoms on drug use and response to substance abuse treatment. 4,5 In view of the high rates of lifetime traumatic event exposure in drug users, it is remarkable that so little is known about rates of trauma re-exposure in this high-risk population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFCWS does not include acute life event stress checklists like those traditionally found in the stress process literature; therefore, some of the more common acute stressors frequently cited in the stress process literature, such as racism, bereavement, or job loss, are not included here. However, the FFCWS does contain many other items that are consistent with these checklists, including marital divorce and separation, imprisonment, and forced sexual activity (for more examples, see Tuner and Lloyd 2004;Peirce et al 2009). Thus, we created two acute life event stress indices (prenatal and postnatal) based on relevant measures to approximate stress checklists.…”
Section: Acute Life Event Stressorsmentioning
confidence: 96%